A Liquid-Based Cytology System, without the Use of Cytocentrifugation, for Detection of Podocytes in Urine Samples of Patients with Diabetic Nephropathy - Moritsugu Kimura; Masao Toyoda; Nobumichi Saito; Noriko Kaneyama; Han Miyatake; Eitaro Tanaka; Hirotaka Komaba; Masanori Hara; Masafumi Fukagawa (Journal of Diabetes Research)
Objective. Podocytes have highly differentiated functions and are extremely difficult to grow; thus, damage of podocytes is associated with glomerular dysfunction. Desquamated podocytes can be detected in urine of patients with severe renal impairment. Unlike the rapidly progressive glomerular damage in glomerulonephritis, only a few desquamated podocytes are usually detected in diabetic nephropathy (DN). It is not clear whether the low podocyte count in DN is due to limitation of the conventional method or true pathological feature. The aim of this study was to compare the conventional method with a newly modified method in detecting podocytes in morning urine samples of patients with DN. Materials and Methods. The study subjects were patients with type 2 diabetes. Urine samples from these patients were analyzed by the conventional method (Cytospin®) and the modified method (SurePath™). We determined the rate of detection of urinary podocytes and the number of detected cells. Results. The detection rate and podocyte count were significantly higher by the modified method than by the conventional method. The differences in the detection rates and numbers of podocytes were not significant between patients with normoalbuminuria and those with macroalbuminuria. However, they were significant in patients with microalbuminuria. The number of podocytes in the urine correlated significantly with the albumin-to-creatinine ratio, but not with the estimated glomerular filtration rate. Conclusions. The true number of urinary podocytes, as measured by the modified SurePath™-based method, in patients with DN is much higher than that estimated by the conventional method.